Investigating the Compliance of Tourism Principles with the Components of Sustainable Tourism: Bangladesh Perspective (Global Journal of Management and Business Research, 2019)
This is a qualitative research that has been done by using secondary data. The main objective of this paper is to examine the compliance of tourism principles of Bangladesh with the components of sustainable tourism that is prepared by the united nation world tourism organization (UNWTO). This paper describes that, Bangladesh has a $421.4 billion travel
Keywords: sustainable tourism; compliance; tourism policy; bangladesh